Human Neonatal Thymus Mesenchymal Stem/Stromal Cells and Chronic Right Ventricle Pressure Overload - Josue Chery; Shan Huang; Lianghui Gong; Shuyun Wang; Zhize Yuan; Joshua Wong; Jeffrey Lee; Sean Johnson; Ming-Sing Si (Bioengineering, 2019)
Right ventricle (RV) failure secondary to pressure overload is associated with a loss of myocardial capillary density and an increase in oxidative stress. We have previously found that human neonatal thymus mesenchymal stem cells (ntMSCs) promote neovascularization, but the ability of ntMSCs to express the antioxidant extracellular superoxide dismutase (SOD3) is unknown. We hypothesized that ntMSCs express and secrete SOD3 as well as improve survival in the setting of chronic pressure overload. To evaluate this hypothesis, we compared SOD3 expression in ntMSCs to donor-matched bone-derived MSCs and evaluated the effect of ntMSCs in a rat RV pressure overload model induced by pulmonary artery banding (PAB). The primary outcome was survival, and secondary measures were an echocardiographic assessment of RV size and function as well as histological studies of the RV. We found that ntMSCs expressed SOD3 to a greater degree as compared to bone-derived MSCs. In the PAB model, all ntMSC-treated animals survived to the study endpoint whereas control animals had significantly decreased survival. Treatment animals had significantly less RV fibrosis and increased RV capillary density as compared to controls. We conclude that human ntMSCs demonstrate a therapeutic effect in a model of chronic RV pressure overload, which may in part be due to their antioxidative, antifibrotic, and proangiogenic effects. Given their readily available source, human ntMSCs may be a candidate cell therapy for individuals with congenital heart disease and a pressure-overloaded RV.